Major Depressive Disorder in Medical Illness: A Review of Assessment, Prevalence, and Treatment Options. Issue 3 (April 2019) - Thom, Robyn; Silbersweig, David A.; Boland, Robert J.
Abstract : ABSTRACT: Major depression, as well as other depressive disorders, is commonly comorbid with other medical illnesses, particularly chronic and systemic medical illnesses. The co-occurrence of the disorders is so common that it challenges our notions of the meaning of comorbidity and our desire to neatly separate psychiatric and medical illnesses. The overlap between symptoms of physical illness and the neurovegetative symptoms of major depression and the initial normative emotional response to physical illness add to the challenge of accurate diagnosis and timely treatment of depression in the medically ill. We review the literature on the comorbidity of depression and the various medical illnesses, including diagnostic and treatment approaches. The differential diagnosis for major depression among medically ill patients should include delirium and medication-induced symptoms. We suggest that major depression itself may be best conceptualized as a systemic illness whose pathophysiology overlaps with other systemic medical illnesses. The initial treatment strategies for major depression in medical illness are like those for the general population; however, the comorbid medical illnesses may interfere with remission. To illustrate these points, we describe a patient with clinical characteristics covered in this review who experienced major depression as well as several chronic illnesses, including hypersensitivity pneumonitis, multiple sclerosis, chronic pain due to degenerative joint disease, and diabetes mellitus.